LUDWIG WITTGENSTEIN: LANGUAGE-GAME AND RELIGIOUS BELIEF - Ottuh, Peter O. O.; Idjakpo, Onos Godwin (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. Wittgenstein’s new understanding of meaning as use has far reaching implications in religion and religious belief. The meaningfulness of language does not depend on the referent but on the actual use of it in the human context. The variety of language uses makes religious language legitimate, and the social character of language makes clear the role of training in religious belief. The characteristic features of religious belief can be summarized as follows: It is an unshakable commitment devoid of evidences and arguments, and it is reasonable only within its framework and grounded on the religious form of life. The rituals that are part of religious beliefs are symbolic and expressive. The existential concerns of human beings reveal a common spiritual nature enabling us to understand other religions and cultures as mirrored in our own humanity.